Procedures as a means of perfecting the environmental management systems - Embros, Grzegorz (Studia Ecologiae et Bioethicae, 2014)
In this paper, the author attempts to point out the meaning of procedures for the environmental management systems (EMS). Particular attention is paid to form and content, as well as the functions, proprieties and structure of the procedures. The analyses were carried out taking into account the systemic approach, with respect to core areas covered by the ISO 14001 standard. Based on the chosen procedures, some fundamental methods of elaborating and implementing the EMS procedures were indicated, which might improve the organization and optimization of realization processes. It was also put forward that procedures should provide a vital support to management processes in fulfilling their purpose.